Ethnography - Singer, Jane B. (Journalism & mass communication quarterly, 2009)
Many qualitative studies in journalism and mass communication research draw on ethnographic methods that originated in anthropology and sociology. These methods involve studying people within their own cultural environment through intensive fieldwork; they emphasize the subjects' frames of reference and understandings of the world. This article uses a comparison between journalism and ethnographic research as a framework for highlighting common problems with manuscripts using this method. It offers veteran ethnographers' tips about what they look for in a manuscript and identifies three ethnographies that are examples of successful application of the method to topics of interest to journal readers.